Analisis Peraturan Daerah Nomor 5 Tahun 2023 Tentang Penanggulangan Kemiskinanan Dalam Mengurangi Kesenjangan Sosial Di Masyarakat (Kemiskinan Di Kota Bajarmasin - Nina Sri Savarina Ulfah; Siti Noormala; Desy Noor Hidayah (Sharia Journal and Education Center Publishing, 2024)
Regional Regulation Number 5 of 2023 on Poverty Alleviation is an effort by the Banjarmasin City government to address the increasing issues of poverty and social inequality. This article analyzes the content and implementation of the regulation, focusing on its effectiveness in reducing social disparities within the community. Using a qualitative approach and document analysis, it is found that this regulation encompasses various programs aimed at improving access to education, health, and job opportunities for the impoverished population. Despite challenges in its implementation, such as a lack of community participation and intersectoral coordination, this regulation is expected to contribute positively to poverty alleviation in Banjarmasin City. The findings provide insights into the role of local policies in creating more equitable social welfare.